(untitled) (Revista de História da UEG (REVHIST), 2025)
This article aims to analyze the historical representations constructed around the image of the Angolan sovereign Nzinga Mbandi. Beyond the portrayals from her time, the goal is to understand Nzinga’s legacy, which transcended the borders of Angola and expanded across subsequent centuries, resonating both in Europe and the Americas, with significant echoes in Brazilian culture. Known as Queen Ginga, she ruled the kingdoms of Ndongo and Matamba for much of the 17th century and was described and represented in multiple and heterogeneous ways—a reflection of the cultural tensions arising from the fact that her gender and positions of power diverged from the paradigms of white European culture. We conclude that her image, re-signified over time, constitutes a symbol of African female strength and leadership, articulating diverse historical contexts. At the intersection between Angola and Brazil, Nzinga’s image emerges as a point of convergence between past and present, where strategies for preserving cultural codes and diaspora languages become evident. Keywords: Angolan context. Representations. Memory. Atlantic. Diaspora.